2004
DOI: 10.1097/01.asn.0000133198.74973.60
|View full text |Cite
|
Sign up to set email alerts
|

High Ambient Glucose Enhances Sensitivity to TGF-β1 via Extracellular Signal—Regulated Kinase and Protein Kinase Cδ Activities in Human Mesangial Cells

Abstract: Abstract. High ambient glucose activates intracellular signaling pathways to induce cytokines such as TGF-␤1 in the extracellular matrix accumulation of diabetic nephropathy. These same pathways also may directly modulate TGF-␤1 signaling. R-Smad phosphorylation, association with Smad4, and nuclear accumulation after TGF-␤1 treatment (1.0 ng/ml) were significantly higher in mesangial cells that were conditioned to 20 mM glucose for 72 h than mesangial cells in 6.5 mM glucose, suggesting that high glucose enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 50 publications
4
60
2
Order By: Relevance
“…TGF-␤ 1 has been reported to enhance the activity of isolated PKC isozymes in various cell types (28,59) and, in particular, PKC-␦ in mesangial cells (19). Differences in the incubation conditions or cell lines used could explain the more widespread PKC activation by TGF-␤ 1 observed in the present experiments compared with the study by Hayashida et al (19). Conversely, high glucose-activated PKC-␤ increases TGF-␤ 1 expression (25).…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…TGF-␤ 1 has been reported to enhance the activity of isolated PKC isozymes in various cell types (28,59) and, in particular, PKC-␦ in mesangial cells (19). Differences in the incubation conditions or cell lines used could explain the more widespread PKC activation by TGF-␤ 1 observed in the present experiments compared with the study by Hayashida et al (19). Conversely, high glucose-activated PKC-␤ increases TGF-␤ 1 expression (25).…”
Section: Discussioncontrasting
confidence: 56%
“…Elevated expression of TGF-␤ 1 is a major stimulant for ECM accumulation by mesangial cells through regulation of genes encoding ECM, PAI-1, and other proteins through Smads and extracellular signal-regulated kinase (ERK) (13,17,18,19,29,36,44,57,68,69,71). In this study, we found for the first time that two initial effects of high ambient glucose, the generation of ROS by NADPH oxidase and activation of PKC-are dependent on signal transduction initiated by TGF-␤ 1 .…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations